2002
DOI: 10.1007/s00497-002-0149-1
|View full text |Cite
|
Sign up to set email alerts
|

Growth and cellular organization of Arabidopsis pollen tubes in vitro

Abstract: Tricellular pollen tubes of Arabidopsis thaliana were cultured in vitro on solid media and studied with respect to growth, cellular organization and ultrastructure, cytoskeletal organization, organelle movement, deposition and structure of the wall and the occurrence of coated pits, all elements assumed to be relevant for tip growth. For our ultrastructural studies we used freeze fixation and freeze substitution. Although Arabidopsis pollen tubes are broadly similar to those of bicellular species such as Nicot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
2
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 18 publications
4
63
2
1
Order By: Relevance
“…The pollen was viewed by UV epiillumination using a Leica DMRB microscope. Pollen germination tests were performed as described (Derksen et al, 2002).…”
Section: Anatomical and Indirect Immunofluorescence Microscopy Of Aramentioning
confidence: 99%
“…The pollen was viewed by UV epiillumination using a Leica DMRB microscope. Pollen germination tests were performed as described (Derksen et al, 2002).…”
Section: Anatomical and Indirect Immunofluorescence Microscopy Of Aramentioning
confidence: 99%
“…Individual open flowers were collected in microtiter plates (TC microwell 96F; Nucleon Biosciences, Glasgow, Scotland) containing 50 L of germination medium (Derksen et al, 2002) per well. Plates were sealed and incubated overnight at 22ЊC under continuous light.…”
Section: Cytological and Phenotypic Analyses Of Pollenmentioning
confidence: 99%
“…Despite such postpollination (progamic) development, which inadvances, progress toward demonstrating their funcvolves rapid directional pollen tube growth within the tional roles is still limited. Reverse genetic approaches female reproductive tissues (reviewed in Pruitt 1999; have shown that pollen germination and tube growth Johnson and Preuss 2002;Lord 2003). Although postdepend upon the gametophytic synthesis of cellular pollination events have been extensively described at components involved in various signaling networks the cellular level, the identification and characterization (Muschietti et al 1994;Kost et al 1999;Li et al 1999; of mutants affecting male progamic phase functions Tang et al 2002), including calcium-mediated signaling remains a challenge because of two major constraints:…”
Section: T He Life Cycle Of Flowering Plants Alternates Betweenmentioning
confidence: 99%
“…Phenotypic analyses of developing microspores and pollen using DAPI staining were performed as described tions, we developed routine genetic and cytological apin Park et al (1998). In vitro germination assays were perproaches that we have applied here to the analysis of 5 formed using conditions modified from Derksen et al (2002) seth mutations. (Hamamatsu Photonics, Japan).…”
Section: Laboratory As Described Inmentioning
confidence: 99%